Foraging preference of barnacle geese on endophytic tall and red fescues - Koski TM; Saikkonen K; Klemola T; Helander M (JACK H BERRYMAN INST, 2022)
Many grasses (Poaceae) have symbiotic fungal endophytes, which affect livestock by producing unpalatable or harmful secondary compounds. Less is known about the repelling effects of fungal endophytes on avian grazers despite potential wildlife management implications. Herbivorous goose (Branta spp.) species may become a nuisance in recreational use areas via fecal littering. Planting these areas with grasses that avian grazers avoid may help mitigate this damage. In 2016, we studied the foraging preference of the barnacle geese (B. leucopsis) with endophytic (E+) or endophyte-free (E-) red fescue (Festuca rubra) and/or tall fescue (Schedonorus phoenix) in 2 sites in Finland that had a history of nuisance geese damage. In the high grazing pressure site, we planted both grass species, while in the low grazing pressure site only tall fescue was used. Geese preference was measured as the percentage of the area grazed, the height of the residual grass grazed, and the number of fecal droppings in the grass plots. Geese foraging did not differ between E- and E+ grasses, but red fescues were preferred over tall fescues. This supports previous findings that tall fescues or other coarse species could reduce the attractiveness of recreational areas to geese.